THE INFLUENCE OF SOIL FERTILISATION WITH ORGANIC MANURE ABOUT SURFACE WATERS - DANA POPA; CARMEN NICOLAE; GABRIELA MALOŞ; R. AL. POPA; G. MALOŞ; ANDRA ŞULER (Scientific Papers Animal Science and Biotechnologies, 2023)
In the hydrographic basin of Mures river, aboard an altitude gradient, were taken samples from surface waters for research the nutrients concentrations. The reference point was represented by a dairy caw farm where the agricultural fields of this is applied the organic fertilization with manure. The water samples were prelevated in spring and autumn and the prelevate dates are the same with spread manure dates. At the second data prelevaion (in autumn) it observed an increase of N-NH4, N-NO3 and P in surface water in comparison with the concentrations founded at first data prelevation (in spring). The explication is the manifestation to the cumulated and at distance effects of introduction in water to some organic products, very probably washed from neighborhoods of agricultural field. Were calculated values of Student test for seasonal comparisons and were founded significant differences between nutrients concentration values at first and second prelevations. These bigger concentrations values of N in water are consequence of wrong manure management.